Sellars vs. McDowell on the Structure of Sensory Consciousness (Diametros, 2010)
I argue that John McDowell’s attempt to refute Wilfrid Sellars’s two-component analysis of perceptual experience and substitute for it a conception according to which perceptual experience is the “conceptual shaping of sensory consciousness” fails. McDowell does not recognize the subtle dialectic in Sellars’s thought between transcendental and empirical considerations in favor of a substantive conception of sense impressions, and McDowell’s own proposal seems to empty the notion of sensory consciousness of any real significance.